Genetics primer for exercise science and health - Roth, Stephen M. 1973- (Primers in exercise science series, 2007)
Genetics Primer for Exercise Science and Health is the first text dedicated to the basic concepts of genetics in relation to the broad range of topics in exercise science and health. Author Stephen M. Roth, PhD, makes the content comprehensible for readers who are unfamiliar with genetics without sacrificing the foundational and critical understanding necessary for interpreting research findings and incorporating genetics into research programs. Genetics Primer for Exercise Science and Health maintains a practical focus and addresses common concerns when preparing to study genetics, such as how to use online search tools to identify existing research literature and how to identify and select candidate genes using genome databases. Through this text, readers will discover these concepts: The basics of DNA and genetics as they relate to health, physical activity, and sport; Specific skills and strategies for interpreting and applying genetics findings in research; How genetics research may affect sport performance training and clinical practice; The ethical issues raised by genetics in society and sport. Special focus sections are incorporated throughout the text, providing expanded discussions of interesting topics in each chapter. Students see examples of how the principles described in the book have played out in real-life research, and they receive explicit instructions on planning and interpreting genetics research. Pedagogical aids such as summaries, key terms, and review questions also make this text ideal for efficient learning. Part I presents readers with the basic biology and genetics information they need in order to understand and apply the information to exercise science. Part II explores the research and design methods that will help readers interpret and apply their findings. Part III addresses some of the current research findings in the area of genetics in exercise and health and discusses current issues in the field, including the potential for misuse of new genetic technologies and the ethics involved in gene doping. Genetics Primer for Exercise Science and Healthis the second volume in Human Kinetics' Primers in Exercise Science series, which provides students and professionals with a nonintimidating basic understanding of the science behind its topic and, where appropriate, how that science is applied. These books are written by leading researchers and teachers in their respective areas of expertise. The authors present in an easy-to-understand manner the essential concepts in dynamic, complex areas of scientific knowledge. The books in the series are ideal for researchers and professionals who need some background in an unfamiliar scientific area. The books also function as accessible basic references for those who will be returning to the material often. This particular book adds a health dimension to the exercise science focus of the series, with discussions on disease- and health-related information. Genetic research will play an important role in the future practice of exercise science and health, requiring students and professionals to have this basic knowledge for success in their careers. Through its practical presentation of current and basic topics, Genetics Primer for Exercise Science and Health makes the case for more universities to introduce genetics courses to their curricula. Having the essential topics of genetics in a single, practical introductory text will facilitate the work of instructors, students, and professionals.